Economic crime and conceptions of trust: offender convenience by organizational opportunity - Gottschalk, Petter (Palgrave Macmillan, 2025)
Economic Crime and Conceptions of Trust explores the intricacies of the contemporary concept of trust in episodes of misconduct through an analysis of workplace deviance and crime. Grounded in detailed examinations of contemporary case studies and bolstered by original comparative fieldwork, the text takes an offender-focused approach, emphasizing the pivotal role of convenience. Adopting an interdisciplinary perspective, the authors seek to enhance and broaden existing understanding of white-collar and corporate criminology, while also highlighting its relevance to strategic management studies. A core argument of the book is that the traditional emphasis on individual actors and notions of trustworthiness when conceptualising white-collar has waned in recent times. The authors’ perspective revisits and builds upon this important foundational concept of late twentieth-century discourse within the discipline, signalling a need for a reassessment and highlighting a number of recent conceptual developments to evaluate and position trust within the twenty-first century globalized business sphere. Petter Gottschalk is Professor in the Department of Leadership and Organizational behaviour at BI Norwegian Business School, Norway. Christopher Hamerton teaches and researches Criminology and Criminal justice in the School of Economic, Social and Political Sciences at the University of Southampton, United Kingdom.